2006
DOI: 10.3200/socp.146.1.31-50
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Big Five Personality Factors and Burnout: A Study Among Volunteer Counselors

Abstract: In the present study of 80 volunteer counselors who cared for terminally ill patients, the authors examined the relationship between burnout as measured by the Maslach Burnout Inventory (C. Maslach, S. E. Jackson, & M. P. Leiter, 1996) and the 5 basic (Big Five) personality factors (A. A. J. Hendriks, 1997): extraversion, agreeableness, conscientiousness, emotional stability, and intellect/autonomy. The results of 3 separate stepwise multiple regression analyses showed that (a) emotional exhaustion is uniquely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
295
3
28

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(351 citation statements)
references
References 54 publications
25
295
3
28
Order By: Relevance
“…Job satisfaction is the opposite dimension of job exhaustion and the researches have shown that there is a strong relation between personality features and job exhaustion. It is reasonable to investigate the relations between personality factors and job satisfaction [10,11]. A part of these features almost traverse a constant process during the lifetime of any individuals and they are less affected by environmental and treatment factors that these features determine basic lines of any individual's personality.…”
Section: Introductionmentioning
confidence: 99%
“…Job satisfaction is the opposite dimension of job exhaustion and the researches have shown that there is a strong relation between personality features and job exhaustion. It is reasonable to investigate the relations between personality factors and job satisfaction [10,11]. A part of these features almost traverse a constant process during the lifetime of any individuals and they are less affected by environmental and treatment factors that these features determine basic lines of any individual's personality.…”
Section: Introductionmentioning
confidence: 99%
“…10 Burnout is defined as a psychological state of mental weariness that often occurs when work stresses become too much for an individual to handle. 5,11 The condition is the combination of 3 distinct dimensions: emotional exhaustion, depersonalization, and decreased personal accomplishment. 12 The burnout model, as described by Maslach and Jackson, 12 illustrates the development of a chronic state of physical and emotional depletion that is accompanied by a reduction in care for clients or patients as well as a negative evaluation of one's worth or accomplishments.…”
mentioning
confidence: 99%
“…Corroborando esse achado, Bakker et al 19 tiveram como resultado em seu estudo que alguns fatores de personalidade moderaram a relação entre o número de experiências negativas e a ocorrência de burnout no trabalho e serviço voluntário, sugerindo que a personalidade pode ajudar a proteger contra riscos conhecidos de desenvolvimento de burnout no trabalho e serviço voluntário. As análises indicaram que a exaustão emocional tem relação direta com a estabilidade emocional (neuroticismo).…”
Section: Discussionunclassified